Ejecución del gasto social y la evolución de la pobreza en el Perú periodo 2015 - 2019 - Díaz Zumaeta, Javier (2023)
Governments use social programs to serve the population living in poverty and extreme poverty. Normally, an increase in social spending should reduce poverty. That is why the current research seeks the association between the execution of social spending and the evolution of poverty in Peru, during the five-year period 2015 - 2019. That is why this Quantitative - Correlational study was carried out, with a Non-Experimental design. It is concluded that social spending is not related to poverty, since the statistical test resulted in a Correlation Coefficient of r = 0.434725411; and a Coefficient of Determination of R2 = 0.188986183. The analysis of the execution of social spending shows that the largest amount of economic resources was given in the Education / Health Program, having reached S/. 207,904.00 million, a figure that means 54.78% of total spending. On the other hand, the Ministry of Development and Social Inclusion - MIDIS executed a budget of S/. 20,250.00 million, with 35.37% going to the Qali Warma Program, equivalent to S/. 7,163.00 million. The next largest expense was made by the Juntos Program with the sum of S/. 4,954.00 million (24.46%). Both poverty and extreme poverty fell in the period studied, but in different proportions. Poverty contracted slightly by -0.62% annual average, and extreme poverty by -5.42% annual average.